2004
DOI: 10.1128/aac.48.3.783-790.2004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Zinc Salts on Respiratory Syncytial Virus Replication

Abstract: Zinc supplementation decreases the morbidity of lower respiratory tract infection in pediatric patients in the developing world. We sought to determine if zinc mediates a specific inhibitory effect against the major cause of pediatric lower respiratory tract disease, respiratory syncytial virus (RSV). We determined the in vitro inhibitory effect of three zinc salts (zinc acetate, lactate, and sulfate) on the replication of RSV at various concentrations of 10 and 1 mM and 100 and 10 M. The degree of inhibition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
126
0
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(132 citation statements)
references
References 27 publications
2
126
0
4
Order By: Relevance
“…Inhibition of DNA replication in S. enteritidis after nitrogen oxide exposure is accompanied by Zn mobilisation, which implies that DNA-binding Zn metalloproteins are critical targets of antimicrobial activity (Schapiro et al, 2003). In accordance with observations in the above studies, electron microscopy studies on HSV have demonstrated massive deposition of Zn onto HSV virions, which interfered with glycoprotein-mediated fusion (Suara and Crowe, 2004).…”
Section: Effects Of Xenobiotics On Host Resistancesupporting
confidence: 67%
See 1 more Smart Citation
“…Inhibition of DNA replication in S. enteritidis after nitrogen oxide exposure is accompanied by Zn mobilisation, which implies that DNA-binding Zn metalloproteins are critical targets of antimicrobial activity (Schapiro et al, 2003). In accordance with observations in the above studies, electron microscopy studies on HSV have demonstrated massive deposition of Zn onto HSV virions, which interfered with glycoprotein-mediated fusion (Suara and Crowe, 2004).…”
Section: Effects Of Xenobiotics On Host Resistancesupporting
confidence: 67%
“…Data also show that Ca causes conformation changes in rotaviruses (Pando et al, 2002), Mn causes changes in virulence of HIV (Vartanian et al, 1999), and Cd reactivates latent HSV (Fawl et al, 1996). Moreover, Zn influences gene expression in CMV (Takekoshi et al, 1993) and replication of respiratory syncytical virus (RSV) (Suara and Crowe, 2004). Consequently, in a host of experimental studies several essential (Ca, Cu, Fe, Mn, Se, and Zn) and non-essential (As, Cd, Hg, and Pb) trace elements have been shown to have the capability to influence growth and virulence of various microorganisms (see section "altered virulence of microorganisms caused by nutrients and xenobiotics").…”
Section: Discussionmentioning
confidence: 93%
“…Zinc, which can inhibit rhinovirus replication and has activity against other respiratory viruses such as respiratory syncytial virus, 8 is a potential treatment for the common cold. The exact mechanism of zinc's activity on viruses remains uncertain.…”
Section: -7mentioning
confidence: 99%
“…30,31 Sama dengan penelitian lain yang menyatakan bahwa pemberian suplementasi seng dapat menghambat kemampuan replikasi dari virus RSV, hasil penelitian secara invitro mendapatkan bahwa seng menghambat replikasi RSV sejak preinkubasi, absorpsi, penetrasi, dan ekskresi. 32 Defisiensi seng dihubungkan dengan atrofi timus, limfopenia, dan penurunan respon imun termediasi sel dan antibodi. Sel epitel timus menghasilkan timulin yang merupakan hormon yang berperan dalam adhesi, migrasi, maturasi, dan peningkatan fungsi sel T. Timulin bergantung pada seng untuk aktivitas biologis yang meliputi induksi perkembangan sel T dan efek anti-inflamasi.…”
Section: Pembahasanunclassified